Replacement of saturated with unsaturated fats had no impact on vascular function but beneficial effects on lipid biomarkers, E-selectin, and blood pressure: results from the randomized, controlled Dietary Intervention and VAScular function (DIVAS) study. Issue 1 (27th May 2015) - Vafeiadou, Katerina; Weech, Michelle; Altowaijri, Hana; Todd, Susan; Yaqoob, Parveen; Jackson, Kim G; Lovegrove, Julie A
ABSTRACT: Background: Public health strategies to lower cardiovascular disease (CVD) risk involve reducing dietary saturated fatty acid (SFA) intake to ≤10% of total energy (%TE). However, the optimal type of replacement fat is unclear. Objective: We investigated the substitution of 9.5–9.6%TE dietary SFAs with either monounsaturated fatty acids (MUFAs) or n–6 (ω-6) polyunsaturated fatty acids (PUFAs) on vascular function and other CVD risk factors. Design: In a randomized, controlled, single-blind, parallel-group dietary intervention, 195 men and women aged 21–60 y from the United Kingdom with moderate CVD risk (≥50% above the population mean) followed one of three 16-wk isoenergetic diets (%TE target compositions, total fat:SFA:MUFA:n–6 PUFA) that were rich in SFAs (36:17:11:4, n = 65), MUFAs (36:9:19:4, n = 64), or n–6 PUFAs (36:9:13:10, n = 66). The primary outcome measure was flow-mediated dilatation; secondary outcome measures included fasting serum lipids, microvascular reactivity, arterial stiffness, ambulatory blood pressure, and markers of insulin resistance, inflammation, and endothelial activation. Results: Replacing SFAs with MUFAs or n–6 PUFAs did not affect the percentage of flow-mediated dilatation (primary endpoint) or other measures of vascular reactivity. Of the secondary outcome measures, substitution of SFAs with MUFAs attenuated the increase in night systolic blood pressure (−4.9 mm Hg, P = 0.019) and reduced E-selectin (−7.8%, P = 0.012). Replacement with MUFAs or n–6 PUFAs lowered fasting serum total cholesterol (−8.4% and −9.2%, respectively), low-density lipoprotein cholesterol (−11.3% and −13.6%), and total cholesterol to high-density lipoprotein cholesterol ratio (−5.6% and −8.5%) ( P ≤ 0.001). These changes in low-density lipoprotein cholesterol equate to an estimated 17–20% reduction in CVD mortality. Conclusions: Substitution of 9.5–9.6%TE dietary SFAs with either MUFAs or n–6 PUFAs did not significantly affect the percentage of flow-mediated dilatation or other measures of vascular function. However, the beneficial effects on serum lipid biomarkers, blood pressure, and E-selectin offer a potential public health strategy for CVD risk reduction. This trial was registered at www.clinicaltrials.gov as NCT01478958.